Characterization of structure and functionality of porous materials - Velasco, Manuel Isaac (2023)
Nuclear magnetic resonance is widely used to probe the dynamics of fluids confined in porous media, where structural and functional properties of complex systems can be determined. The application includes a large variety of research or industrial areas such as medicine, gas and oil extraction, soil studies, the development of materials for drug delivery, and catalysis, among many other applications. This review covers the use of different NMR experiments applied to study the liquid/surface interaction, mobility, tortuosity, pore connectivity, and exchange phenomena in different porous matrixes. This article, included in the special issue devoted to NMR in Latin America, provides a review of the most applied techniques and a summary of different applications carried out at the Universidad Nacional de Córdoba in Argentina.